2018
DOI: 10.1111/jssr.12520
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Strain and Mental Health: The Education‐Contingent Role of Religion

Abstract: This study examines whether dimensions of religious involvement (i.e., perceived divine control, private religious practices, and religious social integration) buffer associations between aspiration strain and mental health outcomes (i.e., psychological distress, loneliness, and optimism). We also test three‐way interactions to determine whether the stress‐buffering effects of religious involvement are amplified among undereducated persons. We test our hypotheses with cross‐sectional survey data from Vanderbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 98 publications
2
34
0
Order By: Relevance
“…, ). Religion and health scholars have also begun to develop and test moderated moderation hypotheses (i.e., three‐way interactions), uncovering contexts in which the stress‐buffering effects of religion are amplified among certain disadvantaged segments of the population, such as the elderly and undereducated (DeAngelis and Ellison ; Jung ). Future studies may benefit from exploring whether similar complex patterns apply to sleep outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…, ). Religion and health scholars have also begun to develop and test moderated moderation hypotheses (i.e., three‐way interactions), uncovering contexts in which the stress‐buffering effects of religion are amplified among certain disadvantaged segments of the population, such as the elderly and undereducated (DeAngelis and Ellison ; Jung ). Future studies may benefit from exploring whether similar complex patterns apply to sleep outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This null finding may be due to measurement error in our SES index. One way to address this issue in the future could be to employ measures that better gauge the distressing elements of diminished social status, such as self‐anchored striving scales or measures of financial strain (DeAngelis ; DeAngelis and Ellison ). On a similar note, our single‐item measure of self‐rated health is limited in certain respects and could be supplemented in future studies with more elaborate and objective health measures (e.g., disease inventories, diagnostic measures, or biomarkers) .…”
Section: Discussionmentioning
confidence: 99%
“…We also know that religious persons often turn to God for support during trying times (Krause ), typically through acts of private prayer (Ellison and Taylor ; Krause ; Sharp ). Finally, research has demonstrated that certain disadvantaged segments of the population, such as lesser educated persons and historically marginalized racial‐ethnic groups, tend to rely on and benefit from religious resources more so than their privileged peers (DeAngelis and Ellison ; Ellison, , ; Ellison and Taylor ; Schieman et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies report that the beneficial effects of religion on mental health are greater for individuals who belong to marginalized social groups (i.e., women, African Americans, individuals with fewer socioeconomic status). Recently, scholars push this line of research forward by assessing whether the moderating effects of religion are also greater for individuals from marginalized social backgrounds (Bierman, Lee, and Schieman ; DeAngelis and Ellison ; Jung ). The current study adds to this nascent body of research by showing that the extent to which secure attachment to God reduces the positive associations between belief in supernatural evil and mental health problems is greater for women compared to men.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, research has shown that the positive association between divine control beliefs and the sense of mattering is stronger among women, African Americans, and individuals with less education (Schieman, Bierman, and Ellison ). More recently, DeAngelis and Ellison () find that perceived divine control reduces the positive association between aspiration strain and psychological distress, but only for individuals with lower levels of education. Collectively, these findings indicate that socially disempowered individuals or groups may rely more heavily on religious resources because they tend to have constrained access to secular‐based resources that can contribute to better mental health.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%